Learning by Doing: Design and Evaluation of a Quality Improvement Curriculum for Pediatric Hospitalists. Issue 5 (September 2020) - Szymusiak, John; McCormick, Andrew
Abstract : Introduction: Quality improvement (QI) is a core competency for Pediatric Hospital Medicine (PHM) and required for maintenance of certification, but many hospitalists lack QI training. This project set out to increase a PHM faculty's QI knowledge and comfort participating in QI projects, while concurrently applying the skills learned to a QI project in the hospital. Methods: We designed a 4-session curriculum utilizing principles of adult learning. Faculty immediately applied learned concepts to a QI project to increase the percentage of patients who were seen by an attending and billed for on the same day as admission to the PHM service. Attitudinal data and scores on the validated Quality Improvement Knowledge Application Tool- Revised knowledge assessment were compared precurriculum and postcurriculum. A manifest content analysis was carried out for qualitative questions. Results: Twenty faculty (83%) completed the preassessment; 15 (63%) completed the postassessment. Respondents showed statistically significant improvements in their perceived ability to participate in QI projects and their Quality Improvement Knowledge Application Tool- Revised scores. The group completed a QI project that increased revenue for the division. Faculty appreciated that the curriculum was applied to a real QI project and felt they would use the new skills in their daily practice. Discussion: This curricular model based on adult learning theory, with immediate application to a real QI project, conclusively showed attitudinal, knowledge-based, and hospital system-level improvements, and was well received by faculty.